Agglomeration economies, competitiveness and entrepreneurial performance - Balázs Páger; Éva Komlósi (European Regional Science Association (ERSA), 2015)
This paper aims to elaborate the role of agglomeration effects on countries' competitiveness and entrepreneurial performance. Our research contributes to the understanding of the relationship that exists between a country's urban system characterized by spatial agglomeration (concentration) or deglomeration (deconcentration) processes, and its competitiveness and entrepreneurial performance, respectively. Urbanization economies refer to considerable cost savings generated through the locating together of people and firms across different industries. It has recently become an axiom that the better performance of global cities, as important nodes of innovation and creativity, is derived from agglomeration effects. This general assumption follows that the more concentrated an urban system of a country, the more competitive and better its entrepreneurial performance. Even though this notion has gained quick and ardent acceptance from practitioners, the related literature shows contradictory results and it has induced a heated debate in academic circles, because it has raised serious doubts about the "bigger is better" theory. We hope to contribute to this debate with our detailed analysis. In order to test our hypothesis empirically, we selected 70 countries and calculated the so called ROXY Index measuring the degree of agglomeration or deglomeration in their urban system. To exemplify country level competitiveness we applied the Global Competitiveness Index (GCI), while the Global Entrepreneurship and Development Index (GEDI) was used to demonstrate country level entrepreneurial performance. Our results affirmed that high concentration of population is only one important factor of competitiveness and entrepreneurial performance while other effects may exist. On the other hand, over- or under-concentration of the population within an urban system does not necessary result in a better outcome.
Keywords: O18; L26; 330; urbanization economies; entrepreneurship; competitiveness; spatial cycles